New materialism and intersectionality making middles matter - Kontturi, Katve-Kaisa; Leppänen, Taru; Mehrabi, Tara; Tiainen, Milla (Routledge, Taylor & Francis Group, 2025)
"New Materialism and Intersectionality: Making Middles Matter advances the interplay of intersectionality theories and feminist new materialisms, arguing that co-constitutive influences between these fields will provide feminist and gender studies scholars with improved tools to analyse markers of difference and identity in 21st century realities. In exploring the intersection of new materialisms and intersectionality studies, the volume puts forward a concept of 'the middle'. It refers to the situation-bound mutual impact of material, social, human, and more-than-human elements in the formation of differences, identities, subject positions, and power relations. The chapters elaborate this understanding of the middle in empirical research concerned with the relational emergence of differences in various social, cultural, artistic and ecological settings. The middle is also proposed as a verb, whereby researchers who practise 'middling' cultivate a capacity to account for the open-ended processes and relationships through which intersectional and materially lived differences unfold and reconfigure in particular contexts. This concept of the middle enriches understandings of how intersectional differences exist and can be studied, and what ethical and political implications they involve. The volume will interest scholars and students working with intersectionality, feminist new materialist, and posthumanist theories across the humanities and the social sciences."
Keywords: Neuer Materialismus; Feminismus; Intersectionality (Sociology); Materialism; Feminism; Intersectionnalité; Matérialisme; Féminisme; materialism (philosophical movement); Aufsatzsammlung